STATISTICAL SUBSTANTIATION OF SNOW LOAD STANDARDS ON BUILDING STRUCTURES (Collection of scientific works «Modern structures of metal and wood», 2021)
Ensuring the reliability and safety of buildings and structures largely depends on a proper understanding of nature and quantitative description and rationing of loads on building structures, including snow loads. These loads on structures have a very complex physical nature and changeable nature,  requiring  knowledge  of  thermodynamic  processes  in  the  atmosphere  and  soil,  physical properties of snow, methods of meteorological observations and climatological description of the terrain, variability of loads, the nature of snow deposition on buildings and structures. Such features are to some extent reflected in the sections of design standards of building structures that contain standards for snow load. Most parameters of snow load norms are probabilistic in nature and require the use of statistical methods to justify them. These methods are constantly changing and evolving along with the regular review of building design codes. Analysis of the evolution of domestic snow load codes together with their statistical substantiation is an urgent task. Materials on snow load have been  published  in  various  scientific  and  technical  journals,  collections  of  articles,  conference proceedings. Access to these publications is difficult, and published reviews of the development of snow load rationing are incomplete and do not include the results of research over the past 15 – 20 years.  The article contains a systematic review of publications in leading scientific and technical journals on the problem of snow load over the 80-year period from the 40s of the twentieth century to the present. The main attention is paid to the analysis of tendencies of development of designing codes concerning changes of territorial zoning and design coefficients, appointment of normative and design values of snow load and involvement in it of experimental statistical data.  There is a high scientific  level  of  domestic  code  DBN  B.1.2-2006  "Loads  and  loadings",  which  have  a  modern probabilistic  basis  and  are  associated  with  the  codes  of  Eurocode.  Scientific  results  that  can  be included in subsequent editions of snow load standards are highlighted.